Durum wheat (Triticum turgidum L. var. durum) root system response to drought and salt stresses and genetic characterization for root-related traits - Luca Bonfiglioli; Ieva Urbanavičiūtė; Mario A. Pagnotta (Frontiers in Plant Science, 2024)
Abiotic stresses such as drought and salt are significant threats to crop productivity. The root system adaptation and tolerance to abiotic stresses are regulated by many biochemical reactions, which create a complex and multigenic response. The present study aims to evaluate the diversity of root responses to cyclic abiotic stress in three modern durum wheat varieties and one hydric stress-tolerant landrace in a pot experiment from seedling to more advanced plant development stages. The genotypes responded to abiotic stress during the whole experiment very differently, and at the end of the experiment, nine out of the 13 traits for the landrace J. Khetifa were significantly higher than other genotypes. Moreover, single sequence repeat (SSR) genetic analysis revealed high polymorphism among the genotypes screened and interesting private alleles associated with root system architecture traits. We propose that the markers used in this study could be a resource as material for durum wheat breeding programs based on marker-assisted selection to increase the vegetal material with high drought and salt stress tolerance and to identify candidates with strong early vigor and efficient root systems. This study provides appropriate genetic materials for marker-assisted breeding programs as well as a basic study for the genetic diversity of root traits of durum wheat crops.